Spontaneous rupture of the esophagus (middle third) - Suiffet, Walter; Guerrero, Omar; Vega, Dardo; Jorge, Ana M (Cirugía del Uruguay, 1973)
lhis is a case of spontaneous rupture of esophagus (middle third) only four such cases are recorded in world literature. It is analyzed and those aspects of highest interest are. considered. In therapy of lesion, cronology is of importance since mínimum pleurostomy should be preferred for evolved cases. Possibility of exclusion of esophagus is considered.